Doping to underperform: the impact of coffee consumption on test scores (2018)
We report results of an experiment that randomly distributed coffee and an herbal infusion with no caffeine to students before a non-experimental midterm (ie: with real incentives). Coffee consumption decreases test scores. This is driven by students who are not habituated to consume coffee and who self-report feeling nervous in similar tests. Regular coffee drinkers do not seem to benefit or lose from coffee consumption except if they are coffee-deprived the day of the exam (in which case they perform worse, consistent with the withdrawal reversal hypothesis).